Effect of Juice Extraction Methods on the Physicochemical Characteristics of Haskap Berry (Lonicera caerulea L.) Products - Khattab, Rabie; Ghanem, Amyl; Su-Ling Brooks, Marianne (Current Nutrition & Food Science, 2016)
Background: Haskap berries (Lonicera caerulea L.) are known for their health benefits and high levels of bioactive compounds. They are processed into different products such as juice, syrup and pressed berries. There is an opportunity to enhance the quality of these products by improving the juice extraction process. Objective: To investigate the effect of conventional and modified juice extraction processes on the physicochemical characteristics of haskap berry products. Methods: Haskap berries were conventionally extracted (thawing–pressing– osmotic treatment–pressing) (process A), until 60, 70, 80 and 82 % juice yield. A modified method (process B) was also explored, where thawing and osmotic treatment were merged into one step followed by a one-time press. The physicochemical characteristics of the end products were compared. Results: The syrup showed significantly higher total soluble solids (TSS) (30.25–38.55 Brix) than the juice (10.05–14.35 Brix). There was a negative correlation between the TSS and the titratable acidity (TA) which increased with the extraction yield. The TA was 1.89–2.18, 1.50–1.82 and 1.31- 1.50 g citric acid/ 100 g in the juice (process A), syrup (process A) and sugar solution (process B), respectively. The pressed berries from process B showed higher total anthocyanin content than those of process A. The extracted liquids and pressed berries from the 60 and 70 % yields had similar qualities. Vitamin C content of the whole frozen fruit (89.11 mg/100 g fresh weight) decreased by 60.21, 79.36 and 82.18 % in the juice, syrup and pressed berries, respectively in process A. Process B, however, could retain significantly more vitamin C in the obtained products. Conclusion: Pressing the haskap berries to 70 % juice yield with process B is recommended for saving time and energy and for more nutritious products.
Keywords: extraction techniques